Serum nitric oxide and pediatric sepsis outcomes - Ronald Chandra; Jose M. Mandei; Jeanette I. Ch. Manoppo; Rocky Wilar; Ari L. Runtunuwu; Phey Liana (Paediatrica Indonesiana, 2014)
Background Sepsis is the complex pathophysiologic responsesof the host against systemic infection. Sepsis can cause severeconditions such as septic shock and multiple organ failure.Although we have a better understanding of the molecular basisof sepsis as well as aggressive therapy, the mortality rate remainshigh, between 20-80%. Nitric oxide (NO) is one of the mediatorsassociated with cardiovascular failure, apoptosis and organdysfunction in sepsis.Objective To evaluate for a possible correlation between NOlevels and outcomes in pediatric sepsis.Methods A prospective cohort study was conducted at thepediatric intensive care unit (PICU) of Prof. Dr. R.D. KandouGeneral Hospital in Manado, from June to November 2012. Fortychildren aged one month to five year old, fulfilled the InternationalPediatrics Sepsis Consensus Conference 2 005 criteria were recruited.Nitrite oxide metabolites (nitrite and nitrate) levels were measuredusing a calorimetric assay kit (CaymanÂ®, Catalog No.780001)from venous blood specimens collected at admission. All patientsreceived antibiotics empirically within an hour of the diagnosis.Outcomes of patients recorded were survivor or died, and lengthof stay in PICU.Results Mann-Whitney U test revealed a significant differencebetween median serum NO levels ins urvivors and those who died(18.60 vs. 36.50 fLM/L, respectively; P= 0.016).Conclusion Serum NO concentration is higher in those whodied than in survivors of pediatric sepsis. Specific NO inhibitionmay be beneficial in decreasing morbidity and mortality in thiscondition.